The effect of private valuation on e-auction revenues - Leung,T; Knottenbelt,W (2011)
In recent years, Internet auctions have become increasingly widespread. The Independent Private Values (IPV) model is widely used in the studying of auction behaviour and plays a fundamental role in many analyses of Internet auction performance. This model assumes privacy and independence, meaning that the private values of buyers are drawn from a common distribution, or in probabilistic terms, the series of values are independent and identically distributed. Since a general stochastic analysis is intractable, the IPV model has a significant impact on auction behaviour. In this paper, we study auction performance using an auction process simulator, considering both the hard close and soft close types of Internet auctions. From our experimental findings, we are able to establish quantitative relationships between the different auction process parameters, and also to deploy suitable IPV distributions in modelling the characteristics of different communities of bidders. © 2011 Springer-Verlag.